The 2013 ACC/AHA risk score and subclinical cardiac remodeling and dysfunction: Complementary in cardiovascular disease prediction. (15th December 2019) - Cauwenberghs, Nicholas; Hedman, Kristofer; Kobayashi, Yukari; Vanassche, Thomas; Haddad, Francois; Kuznetsova, Tatiana
Abstract: Background: Echocardiography might enhance cardiovascular (CV) risk stratification beyond tools grading the risk for atherosclerotic CV diseases (ASCVD). We therefore studied the complementarity between the ASCVD risk score recommended by American cardiology societies and echocardiographic profiling in predicting adverse CV outcome in the community. Methods: 984 community-dwelling individuals between 40 and 79 years old (51.3% women) underwent CV risk profiling and echocardiography. We estimated their 10-year ASCVD risk from baseline risk factors using the Pooled Cohort Equations. Participants were categorized as at low (<2.5%), borderline (2.5-<7.5%) or intermediate-to-high (≥7.5%) ASCVD risk. Main outcome was the incidence of CV events collected on average 7.5 years later. Results: The probability for cardiac remodeling and/or dysfunction as assessed by echocardiography rose progressively with increasing 10-year ASCVD risk. During follow-up, 116 participants experienced at least one CV endpoint (15.8 events per 1000 person-years). With increasing 10-year ASCVD risk, the CV event rate increased stronger in participants with ≥1 LV abnormality at baseline. Indeed, in individuals with an intermediate-to-high ASCVD risk and ≥1 LV abnormality at baseline, the risk was significantly higher than the average population risk for a first CV event (HR: 3.00, P < 0.001). Adding the presence of ≥1 LV abnormality to a ASCVD risk score-based model yielded significant improvement in C-statistics ( P = 0.024), integrated discrimination ( P = 0.0085) and net reclassification ( P < 0.001) for adverse CV events. Conclusions: Echocardiographic profiling enhanced CV risk stratification in individuals at intermediate-to-high ASCVD risk. Echocardiographic screening might supplement traditional ASCVD risk grading for CV disease prediction. Highlights: High 2013 ACC/AHA risk score coincided with the presence of cardiac abnormalities. Echocardiography enhanced CV disease prediction in intermediate-to-high risk subjects. Echocardiographic screening might supplement ASCVD risk scoring for CV disease prediction.